2013
DOI: 10.1038/bjc.2013.620
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of docetaxel, cisplatin and 5FU chemotherapy in locally advanced and metastatic penis cancer (CRUK/09/001)

Abstract: Background:Penis cancer is rare and clinical trial evidence on which to base treatment decisions is limited. Case reports suggest that the combination of docetaxel, cisplatin and 5-flurouracil (TPF) is highly active in this disease.Methods:Twenty-nine patients with locally advanced or metastatic squamous carcinoma of the penis were recruited into a single-arm phase II trial from nine UK centres. Up to three cycles of chemotherapy were received (docetaxel 75 mg m−2 day 1, cisplatin 60 mg m−2 day 1, 5-flurouraci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(66 citation statements)
references
References 15 publications
4
59
0
3
Order By: Relevance
“…Active agents include 5‐fluoracil, bleomycin, methotrexate, and cisplatin, used either as single agents or in various combinations. Few randomized trials have compared the benefit of combination over single agent therapy, and although some combinations seem more effective than single agents, toxicity may be substantial (Di Lorenzo et al, ; Carthon et al, ; Nicholson et al, ). Objective response rates range from 20 to 70%, but are usually short lived (4‐6 months) (Shammas et al, ; Haas et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Active agents include 5‐fluoracil, bleomycin, methotrexate, and cisplatin, used either as single agents or in various combinations. Few randomized trials have compared the benefit of combination over single agent therapy, and although some combinations seem more effective than single agents, toxicity may be substantial (Di Lorenzo et al, ; Carthon et al, ; Nicholson et al, ). Objective response rates range from 20 to 70%, but are usually short lived (4‐6 months) (Shammas et al, ; Haas et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these are changing; for example, investigators in the United Kingdom were able to enroll 29 patients on a prospective phase II study in just 15 months. 6 This was facilitated by the designation of 9 regional specialty centers for the treatment of all patients with penile cancer in that country. It is now feasible to conduct a large randomized trial such as the proposed InPACT trial.…”
Section: Resultsmentioning
confidence: 99%
“…Despite preliminary data suggesting that addition of docetaxel to 5-FU and cisplatin was uniquely effective, 11 the response rate in a completed prospective study of TPF was only 38.5%, with grade 3 or grade 4 toxicities experienced by 65.5% of the patients. 6 Based on these data, TPF has not been recommended for routine use.…”
Section: Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…13,15 A phase II clinical trial using docetaxel (XT), CDDP and fluorouracil (5-FU) reported a response rate of 38.5%, but 65.5% of patients in this study experienced severe or life-threatening toxicities. 16 In the phase II clinical trial by Pagliaro et al , 4 cycles of TIP in patients with N2 or N3 disease without distant metastasis produced clinically significant responses in 50% of patients with 53% experiencing grade 3 or 4 adverse events. 9 The patient in our first case tolerated TIP well and achieved CR with pathology showing only granulomatous tissue post-chemotherapy.…”
Section: Discussionmentioning
confidence: 99%